2009
DOI: 10.1002/jnr.22205
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low‐density lipoprotein (oxLDL)‐induced cell death in dorsal root gangion cell cultures depends not on the lectin‐like oxLDL receptor‐1 but on the toll‐like receptor‐4

Abstract: DRG cells have been found to undergo apoptosis and necrosis after oxidized low-density lipoprotein (oxLDL) stimulation in vitro. However, the mechanism of oxLDL-induced DRG cell death is unclear. For this reason, we studied the expression of two potential oxLDL receptors: lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) and toll-like receptor-4 (TLR4) in dorsal root ganglion (DRG) cell cultures from postnatal rats. Cells were cultivated with and without oxLDL. In oxLDL-treated DRG cell cultures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…Together, these results demonstrate that oxLDL up-regulates BMP-2 production in human CAECs through a mechanism dependent on TLR2 and TLR4. In this regard, cell death in dorsal root ganglion cell culture induced by oxLDL is attributed to TLR4, not LOX-1 (16). Our further experiments using immunostaining found that oxLDL is co-localized with TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Together, these results demonstrate that oxLDL up-regulates BMP-2 production in human CAECs through a mechanism dependent on TLR2 and TLR4. In this regard, cell death in dorsal root ganglion cell culture induced by oxLDL is attributed to TLR4, not LOX-1 (16). Our further experiments using immunostaining found that oxLDL is co-localized with TLR2 and TLR4.…”
Section: Discussionmentioning
confidence: 50%
“…Interestingly, minimally modified LDL induces macrophage actin polymerization and cell spreading via a TLR4-dependent mechanism (14). Further, oxLDL induces cell death in ganglion culture in a TLR4-dependent fashion (16). These studies indicate a role for TLR4 in mediating the effect of oxLDL.…”
Section: Oxldl Induces a Pro-osteogenic Response In Human Caecs-mentioning
confidence: 92%
“…Recently, it was demonstrated that oxidized low density lipoprotein (oxLDL), which bind to the scavenger receptor B family member CD36, can promote sterile inflammation through activation of TLR4/6 heterodimer on macrophages (56). Both cell death (57, 58) and foam-cell formation (59) have also been shown to be induced by oxidized LDL through TLR4 in macrophages. Furthermore, oxidized phospholipids from minimally modified low density lipoprotein (mmLDL), which contain essentially the same phospholipids as oxLDL, stimulate macrophage ROS generation (60), ERK activation (61), membrane spreading (62), and inhibition of phagocytic uptake of apoptotic bodies (62), through a partially TLR4-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…15,18 The oxidised lipoproteinsdependent activation of these receptors either triggers apoptosis or survival autophagy in endothelial or granulosa cells. 14,18,19 Ob/ob ovaries could respond to lipid droplet accumulation by upregulation of LOX-1 and/or TLR4 resulting in the cell damage. If so, follicular atresia is not because of leptin-deficiency only.…”
Section: Introductionmentioning
confidence: 99%